QUANTITATIVE PHYTOCHEMICAL SCREENING, THIN-LAYER CHROMATOGRAPHY ANALYSIS, HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FINGERPRINTING, AND ANTIOXIDANT ACTIVITY OF LEAVES OF DIOSPYROS MONTANA (ROXB.) - V PURI, ABHIJEET (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate important phytochemical constituents and antioxidant potential of Diospyros montana Roxb. leaves belonging to the family Ebenaceae. Methods: Leaves were exhaustively extracted with ethanol and fractionated into petroleum ether, chloroform, and ethyl acetate extracts. The various fractions were further analyzed for phytochemical composition and concentration-dependent antioxidant activity using conventional methods and high-performance thin-layer chromatography (HPTLC) fingerprinting. Since leaves contained phenolic compounds, extracts were evaluated for total phenolic content, flavonoids contents, and in-vitro antioxidant activity. Antioxidant potential was assessed using parameters such as superoxide radical scavenging, nitric oxide inhibition, and β-carotene/linoleic acid antioxidant activity. Results: Primitive phytochemical investigation highlighted the presence of steroids, saponins, flavonoids, alkaloids, and tannins which were confirmed by TLC and HPTLC fingerprinting. The antioxidant activity of leaf extracts decreased in the following order ethyl acetate > ethanolic > chloroform > petroleum ether and it was comparable with standards such as ascorbic acid and butylated hydroxytoluene. Conclusion: The present study concludes that the ethanolic extract and fractions of D. montana (Roxb.) leaves have prominent antioxidant activity comparable to standards. Therefore, D. montana (Roxb.) leaves may be used as a probable source of natural antioxidants in the pharmaceutical industry.